The Contribution of Fintech to Strengthening SME Financing Access: Evidence from Majene Regency - Syamsuddin, Fajar Rakasiwi; Said, Samsuardi; Riva'i, Dian Rahmayanti; Anfas, Anfas; Wulandari, Futri Ayu (International Journal of Economics Development Research (IJEDR), 2025)
The rapid growth of financial technology (fintech) has brought significant changes to access to financing for small and medium enterprises (SMEs) in Indonesia, particularly in areas with limited conventional banking services. This study aims to analyse the impact of fintech on improving SME access to financing in Majene Regency, West Sulawesi. Using a mixed methods approach, quantitative data was collected from 165 SME actors through structured questionnaires, while qualitative data was obtained through in-depth interviews with selected informants. The variables examined included ease of use, fintech service features, and access to financing, which were analysed using multiple linear regression (SPSS 27) and thematic analysis (NVivo). The results showed that ease of use and fintech service features had a significant positive effect on SME access to financing. The majority of respondents stated that fintech applications—especially QRIS and digital wallets—greatly facilitated transactions and business management. However, there are still obstacles in the form of uneven digital literacy and unstable network infrastructure, so that the use of digital financing features is not yet optimal. This study concludes that the development of inclusive and user-friendly fintech solutions, accompanied by broader digital literacy programmes, is crucial to maximising the role of fintech in supporting regional SMEs. These findings have important implications for fintech providers, local governments, and policymakers in designing effective strategies to strengthen SME growth through digital financial inclusion.